Cellular transformation may be a most promising approach for the treatment of diseases: A hypothesis. (September 2022) - Chu, Ting; Yang, Maosheng
Abstract: The main purpose of this work is to propose a novel approach for the treatment of human diseases. Evidence suggested that cellular transformation may be one of the most promising approaches for the treatment of diseases. Therefore, we hypothesize that cellular transformation may be a most promising approach for the treatment of diseases. We believe that this hypothesis above may has a significant impact on the treatment of diseases, the medical research and development, the medical education, and the life science research; which can be reflected in the following: (1) It can transform cells of various pathological states into normal tissue cells without toxicity or adverse effects on surrounding normal tissue cells; (2) It can replace the chemical drug treatment of diseases, and eliminate patient's suffering induced by chemical poisoning; (3) It will help to change human cognition and concept of treating diseases, thereby advancing the development of medicine; (4) It will help advance the revision of medical textbooks, and help train a new generation of medical talents for the benefit of all mankind; and (5) It will help advance the understanding or elucidation of the life phenomena of human beings. Hence, we believe that this hypothesis above is worthy of extensive and in-depth study and discussion in the future.